2017
DOI: 10.7759/cureus.1095
|View full text |Cite
|
Sign up to set email alerts
|

Serial Magnetic Resonance Imaging in Creutzfeldt-Jakob Disease: a Case Report and Literature Review

Abstract: Creutzfeldt-Jakob disease (CJD) is a rare, degenerative, invariably fatal brain disorder. CJD usually appears in later life and runs a rapid course. Typically, the onset of symptoms occurs about age 60 and about 90% of individuals die within one year. We report a case of 67-year-old male presented with progressive aphasia, confusion, dysphagia and inability to carry out activities of daily life (ADLs) over a period of three to four weeks. The patient had past medical history of chronic atrial fibrillation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…The hyperintensity was more evident on DWI than FLAIR (Fluid‐attenuated inversion recovery), and the restricted diffusion was noted on ADC 3,4 . One study showed that a serial MRI scan within the disease course is necessary for reaching the diagnosis of CJD 5 . Cortical DWI hyperintensity with normal ADC mapping has been reported in autoimmune encephalitis(AE), which is a key neuroimaging clue to distinct AE from sCJD 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperintensity was more evident on DWI than FLAIR (Fluid‐attenuated inversion recovery), and the restricted diffusion was noted on ADC 3,4 . One study showed that a serial MRI scan within the disease course is necessary for reaching the diagnosis of CJD 5 . Cortical DWI hyperintensity with normal ADC mapping has been reported in autoimmune encephalitis(AE), which is a key neuroimaging clue to distinct AE from sCJD 6 .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 One study showed that a serial MRI scan within the disease course is necessary for reaching the diagnosis of CJD. 5 Cortical DWI hyperintensity with normal ADC mapping has been reported in autoimmune encephalitis(AE), which is a key neuroimaging clue to distinct AE from sCJD. 6 A PET-CT scan is useful for improving diagnostic accuracy by showing a hypometabolic pattern in CJD patients.…”
Section: Discussionmentioning
confidence: 99%
“…CJD is diagnosed by afflicted cornea, larger and progressive putamen and whole atrophy and ventricular dilatation in its delayed phase. Performing MRI frequently cannot be used as a definitive diagnostic tool for CJD; however, studies show that in addition to diagnosis, it helps in monitoring the disease [ 10 ]. MRI protocol includes sagittal FLAIR with a 3mm cross section, T2- weighted with 3mm cross section, T1- weighted, and DWI, ADC map.…”
Section: Discussionmentioning
confidence: 99%
“…EEG is a definitive tool for CJD diagnosis. The periodic pattern of sharp two or three-phase wave complexes is seen in 67 to 95% of cases of the sporadic form [ 10 ]. Our patients met these CJD criteria; their MRI and EEG results confirmed our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical criteria for CJD mentioned by the center for preventing and controlling diseases [12] CJD is diagnosed by afflicted cornea, larger and progressive putamen and whole atrophy and ventricular dilatation in its delayed phase. Performing MRI frequently cannot be used as a definitive diagnostic tool for CJD; however, studies show that in addition to diagnosis, it helps in monitoring the disease [10]. MRI protocol includes sagittal FLAIR with a 3mm cross section, T2-weighted with 3mm cross section, T1-weighted, and DWI, ADC map.…”
Section: Discussionmentioning
confidence: 99%